Great expectations - Geary, Rick.; Dickens, Charles, 1812-1870. (New York, N.Y. : Berkley ; [Chicago, Ill.] : First Pub., 1990)
After harsh early years, Pip, an orphan growing up in Victorian England, is given the means to become a gentleman by an unknown benefactor and learns that outward appearances can be deceiving. Presented in comic book format.
Keywords: Orphans -- Fiction; Coming of age -- Fiction; Great Britain -- History -- 19th century -- Fiction; Cartoons and comics